Solar Lighting Technologies for Highway Green Rest Areas in China: Energy Saving Economic and Environmental Evaluation - Xiaochun Qin; Qingchao Wei; Lianjun Wang; Yi Shen (International Journal of Photoenergy, 2015)
In this paper, taking Lushan West Sea highway green rest area in Jiangxi Province of China as the case study, the suitable types, applicability, advantages, and effective methods of solar lighting technologies for highway rest area were determined based on the analysis of characteristics of highway green rest area. It was proved that solar lighting technologies including the natural light guidance system, solar LED lighting, and maximizing natural light penetration were quite suitable for highway rest area in terms of lighting effects and energy and economic efficiency. The illuminance comparison of light guidance system with electrical lighting was made based on the on-site experiment. Also, the feasibility of natural light guidance system was well verified in terms of the lighting demand of the visitor centre in the rest area by the illuminance simulation analysis. The evaluation of the energy saving, economic benefits, and environmental effects of solar lighting technologies for highway rest area was, respectively, made in detail. It was proved that the application of solar technology for green lighting of highway rest facilities not only could have considerable energy saving capacity and achieve high economic benefits, but also make great contributions to the reduction of environment pollution.